ALAS: agent-oriented domain-specific language for the development of intelligent distributed non-axiomatic reasoning agents. Issue 8 (21st October 2018) - Sredojević, Dejan; Vidaković, Milan; Ivanović, Mirjana
ABSTRACT: This paper presents an extension of the agent-oriented domain-specific language ALAS to support Distributed Non-Axiomatic Reasoning. ALAS is intended for the development of specific kind of intelligent agents. It is designed to support the Siebog Multi-Agent System (MAS) and implementation of the Siebog intelligent agents. Siebog is a distributed MAS based on the modern web and enterprise standards. Siebog offers support to reasoning based on the Distributed Non-Axiomatic Reasoning System (DNARS). DNARS is a reasoning system based on the Non-Axiomatic Logic (NAL). So far, DNARS-enabled agents could be written only in Java programming language. To solve the problem of interoperability and agent mobility within Siebog platforms, the ALAS language has been developed. The goal of such language is to allow programmers to develop intelligent agents easier by using domain specific constructs. The conversion process of ALAS code to Java code is also described in this paper.